Design and fabrication of diffractive atom chips for laser cooling and trapping - Cotter,JP; McGilligan,JP; Griffin,PF; Rabey,IM; Docherty,K; Riis,E; Arnold,AS; Hinds,EA (Applied Physics B, 2016)
It has recently been shown that optical reflection gratings fabricated directly into an atom chip provide a simple and effective way to trap and cool substantial clouds of atoms (Nshii et al. in Nat Nanotechnol 8:321–324, 2013; McGilligan et al. in Opt Express 23(7):8948–8959, 2015). In this article, we describe how the gratings are designed and microfabricated and we characterise their optical properties, which determine their effectiveness as a cold atom source. We use simple scalar diffraction theory to understand how the morphology of the gratings determines the power in the diffracted beams.